2016
DOI: 10.1016/j.lfs.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

KatG and KatE confer Acinetobacter resistance to hydrogen peroxide but sensitize bacteria to killing by phagocytic respiratory burst

Abstract: Aims Catalase catalyzes the degradation of H2O2. Acinetobacter species have four predicted catalase genes, katA, katE, katG, and katX. The aims of the present study seek to determine which catalase(s) plays a predominant role in determining the resistance to H2O2, and to assess the role of catalase in Acinetobacter virulence. Main Methods Mutants of A. baumannii and A. nosocomialis with deficiencies in katA, katE, katG, and katX were tested for sensitivity to H2O2, either by halo assays or by liquid culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 40 publications
4
66
0
Order By: Relevance
“…The significant differences in expression of iron acquisition genes seen here are consistent with those previously observed in A. baumannii (25) and other bacteria (26) and provide evidence for coordinated expression of genes related to iron homeostasis.…”
Section: Discussionsupporting
confidence: 89%
“…The significant differences in expression of iron acquisition genes seen here are consistent with those previously observed in A. baumannii (25) and other bacteria (26) and provide evidence for coordinated expression of genes related to iron homeostasis.…”
Section: Discussionsupporting
confidence: 89%
“…It is worth mentioning that, similar to the observations in Xanthomonas campestris (Jittawuttipoka et al ., ), although several assays revealed that KatA was the major catalase in E. amylovora , the KatG‐deficient mutant was more affected during plant–pathogen interactions. In this sense, the importance of KatG might be related to functions other than catalase activity, such as the neutralization of toxic peroxide compounds produced after H 2 O 2 exposure (McLean et al ., ; Sun et al ., ). Our results correlate well with katG induction during fruit infection (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The antioxidant enzyme catalase plays a vital role in protecting A. baumannii from damage produced by reactive oxygen species through hydrolyzing hydrogen peroxide (Jones et al 2017). The katE gene is responsible for catalase enzyme production in A. baumannii, which is under the control of QS (Bhargava et al 2015;Montagu et al 2016;Sun et al 2016). The real-time data exposed notable down regulation of katE gene expression in PCCs treated A. baumannii (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…; Sun et al . ). The real‐time data exposed notable down regulation of katE gene expression in PCCs treated A. baumannii (Fig.…”
Section: Discussionmentioning
confidence: 97%